Stereotactic MR-Guided Radiotherapy for Pancreatic Tumors: Dosimetric Benefit of Adaptation and First Clinical Results in a Prospective Registry Study - Michalet, Morgan; Bordeau, Karl; Cantaloube, Marie; Valdenaire, Simon; Debuire, Pierre; Simeon, Sebastien; Portales, Fabienne; Draghici, Roxana; Ychou, Marc; Assenat, Eric; Dupuy, Marie; Gourgou, Sophie; et al. (Frontiers in Oncology, 2022)
Stereotactic MR-guided Adaptive RadioTherapy (SMART) is an attractive modality of radiotherapy for pancreatic tumors. The objective of this prospective registry study was to report the dosimetric benefits of daily adaptation of SMART and the first clinical results in pancreatic tumors. All patients treated in our center with SMART for a pancreatic tumor were included. Patients were planned for five daily-adapted fractions on consecutive days. Endpoints were acute toxicities, late toxicities, impact of adaptive treatment on target volume coverage and OAR sparing, local control rate, distant metastasis-free survival (DMFS) and overall survival (OS). Thirty consecutive patients were included between October 2019 and April 2021. The median dose prescription was 50 Gy. No patients presented grade > 2 acute toxicities. The most frequent grade 1-2 toxicities were asthenia (40%), abdominal pain (40%) and nausea (43%). Daily adaptation significantly improved PTV and GTV coverage and OAR sparing. With a median follow-up of 9.7 months, the median OS, 6-months OS and 1-year OS were 14.1 months, 89% (95% CI: (70- 96%) and 75% (95% CI: (51- 88%), respectively from SMART completion. Local control at 6 months and 1 year was respectively 97 % (95% CI: 79 – 99.5%) and 86% (95% CI: 61 – 95%). There was no grade > 2 late toxicities. With a median follow-up of 10.64 months, LAPC and Borderline Resectable Pancreatic Cancers (BRPC) patients (22 patients) had a median OS, 6-months OS and 1-year OS from SMART completion of 14.1 months, 76% (95% CI: (51- 89%) and 70% (95% CI: (45- 85%), respectively. Nine patients underwent surgical resection (42.1% of patients with initially LAPC and 33.3% of patients with BRPC), with negative margins (R0). Resected patients had a significantly better OS as compared to unresected patients (p= 0.0219, HR = 5.78 (95% CI: 1.29-25.9)). SMART for pancreatic tumors is feasible without limiting toxicities. Daily adaptation demonstrated a benefit for tumor coverage and OAR sparing. Acute and late toxicities were low. OS and LC rate were promising. SMART achieved high secondary resection rate in LAPC patients. Surgery after SMART seemed to be feasible and might increase OS in these patients.